The Effect of Light Emitting Diode (LED) White and Blue Spectrum on The Characteristics of Lettuce Grown in The Deep Flow Hydroponic: Deep Flow Hydroponic of Lactuca - Sihotang, Yosua P; Indriyani, Indriyani; Fortuna, Dewi (PUI BiGME Universitas Jambi, 2023)
Lettuce, which is also known by the scientific name Lactuca sativa L, is a promising horticultural crop and has high economic value. This plant is rich in minerals, vitamins, antioxidants, potassium, iron, folate, carotene, vitamin C and vitamin E. In growing lettuce hydroponically, the Deep Flow Technique (DFT) method has proven to be effective. This research used a Randomized Block Design (RAK) to test the effect of giving white and blue LED spectrum to lettuce plants. There were four treatments tested: P1 (no LED), P2 (1:3 white and blue LED), P3 (1:1 white and blue LED), and P4 (3:1 white and blue LED). Each treatment was repeated five times, with two sample plants in each repetition, so that there were a total of 40 sample plants. The parameters involve plant height, number of leaves, root length, root weight, leaf color, antioxidant content, consumption weight, leaf width, stem diameter, and electricity consumption during harvest. Measurements were carried out every week for five weeks. The results showed that LED lights had a significant effect on the number of leaves, stem diameter, root weight and consumption weight, but did not have a significant effect on plant height, leaf width, root length, antioxidant content and leaf color. Based on this research, it can be concluded that treatment 4 (white and blue LED 3:1) gave the best results, with the number of leaves reaching 27.4 pieces, root length 18.95 cm, root weight 23.2 g, consumption weight 109 g, stem diameter 8.2 mm, and antioxidant content of 42.39% inhibition. Keywords: Sungkai leaves, herbal tea, brewing temperature, brewing time. Keywords:Deep Flow Technique, Hidroponik, Light Emitting Diode, Selada